Analisis Faktor-Faktor yang Mempengaruhi Prestasi Mahasiswa Departemen Statistika IPB menggunakan Metode SEM-PLS - Zunita Sari; Muhammad Nur Aidi; La Ode Abdul Rahman (Xplore: Journal of Statistics, 2019)
Education is improving human power. Education is divided into three level namely primary, secondary and high level education. High level education can be obtained from University. University as one of high level education, is a formal education place for all studying and teaching activities, research, community service and develop scientific student to become qualified workforce. Student achievement in universities is influenced by various factors that cannot be measured both direct and indirect. The method that is used to determine those factors is structural equation modeling (PPS) with partial least square (PLS) method. PPS with PLS method used when there are some assumptions on diverse PPS which is not fullfiled, like binormal distribution and the big ammount of examples. The results showed that the six exogenous latent variables (family background, motivation, environment, visual learning style, auditory learning style, and kinesthetic learning style) did not have a significant influence on endogenous variables (student achievement). The model used in this study has a R2 value 14.1%. This values ​​indicates that the model built is still weak in explaining the diversity of student achievement.